2021
DOI: 10.1186/s43161-021-00026-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of structured physical therapy intervention on functional recovery in a patient with CAPOS syndrome: a case report

Abstract: Background CAPOS syndrome (cerebellar ataxia, areflexia, pescavus, optic atrophy, and sensorineural hearing loss) is a rare congenital autosomal dominant disorder. The resulting neurological sequelae of impairments are progressive in nature and may interfere with functional independence, performing activities of daily living (ADL’s), and subsequently, affecting the quality of life (QOL). Since it is an extremely rare disorder, there is a severe dearth in the literature about how specific physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In structured physiotherapeutic program, Frenkel's exercises, namely perception, precision, practice, peak performance and progression and diagonal PNF patterns were incorporated during the intervention to achieve functional movement synergies. [7] The home based exercise regimen was focused on balancing exercises such as side to side weight transfer, foot circles, forward reach, toe touches. Further, the findings of the present study revealed that both structured physiotherapeutic program as well as home based exercise regimen, are equally effective in diminishing the affection of ataxia in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In structured physiotherapeutic program, Frenkel's exercises, namely perception, precision, practice, peak performance and progression and diagonal PNF patterns were incorporated during the intervention to achieve functional movement synergies. [7] The home based exercise regimen was focused on balancing exercises such as side to side weight transfer, foot circles, forward reach, toe touches. Further, the findings of the present study revealed that both structured physiotherapeutic program as well as home based exercise regimen, are equally effective in diminishing the affection of ataxia in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The final score was the time in seconds of the quicker of two timed trials. [7] : The patients were administered six therapy sessions per week for a total duration of 4 weeks with each therapy session lasting for 60 minutes, with appropriate rest intervals. The detailed description of exercise intervention in this program has been included in Table 1.…”
Section: Methodsmentioning
confidence: 99%